More&More: The Invisible Oceans - Zurkow, Marina (punctum books, 2016)
More&More is an art and research project that explores the language and mechanics of global trade, container shipping, and the exchange of goods. It questions a mercantile structure that by necessity disallows the presence of ocean as a real space in order to flatten the world into a Pangaea of capital. The project is presented in two volumes, released in conjunction with an exhibition of Marina Zurkow's work (with collaborators Sarah Rothberg, Surya Mattu, and others) at bitforms gallery in New York City in February 2016. This book, More&More (The Invisible Oceans), is a catalog of the exhibition, featuring many full-color images of the art on display (including video stills, bespoke bathing suits, and fungal sculptures), as well as an introduction by Marina Zurkow and a conversation between Zurkow and international curator Kathleen Forde. Its companion book, More&More (A Guide to the Harmonized System), is an experimental "brick" of a book that intervenes in the Harmonized Commodity Description and Coding System (also known as the HS Code). The HS Code is the internationally accepted standard of product classification, which codifies the way nations conduct import/export. All legal trade products (and illegal ones that find loopholes) are shipped using this system. More&More (A Guide to the Harmonized System) lists the astonishing variety of items that are shipped around the world, and includes instructions for using the code to ship items (both legally and illegally). It also includes poetic, personal, and scholarly annotations by Stacy Alaimo, Heather Davis, Kathleen Forde, Dylan Gauthier, Elena Glasberg, Calliope Mathios, Steve Mentz, Astrida Neimanis, Chris Piuma, Elspeth Probyn, Sarah Rothberg, Phil Steinberg, Rita Wong, and Marina Zurkow.